Upaya Pencegahan Stunting dan Potensi Tumbuh Kembang Anak - Abd. Mukhsin Mukhsin; Dini Rahmawati Nasution,; Mazidatul Farha; Mustika Mustika; Zuhra Nahda (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Stunting is a developmental disorder experienced by children due to poor nutrition, repeated infections, and inadequate psychosocial stimulation. Stunting is a condition in which children experience growth disorders as a result of insufficient nutritional intake for a relatively long time, causing the child's height to not match his age. Some of the factors that cause stunting are the practice of giving colostrum and exclusive breastfeeding, children's consumption patterns, and infectious diseases, access and availability of food ingredients as well as environmental sanitation and health. Stunting that has occurred if it is not balanced with catch-up growth results in decreased growth, the problem of stunting is a public health problem associated with an increased risk of illness, death and inhibition of both motor and mental growth. Keywords: Children, Prevention, Stunting